Pengaruh Model Pembelajaran ARIAS mengunakan Metode Eksperimen terhadap Hasil Belajar Fisika - Khusnul Khatimah; I Wayan Darmadi; Darsikin Darsikin (Jurnal Kreatif Online, 2021)
This research was conducted with the aim of looking at the effect of learning outcomes on physics taught using the ARIAS learning model using the experimental method. This type of research is a quasi-experimental design with a non-randomized pretest-posttest control group. The population of this study were all students of class X SMA Negeri 1 Dampal Selatan. Sampling technique used in this research is Proposive Sampling. The physics learning outcome instrument is in the form of a multiple choice test that has been validated through construct validity. The test of physics learning outcomes obtained showed that the average score of the experimental group was 16.75 which was higher than the control group, which was 12.07. Hypothesis test T-test (two parties), obtained tcount=6.69 and ttable(0.975(68))=1.99 at a significance level of a=0.05. This means that there is an effect on student learning outcomes using the ARIAS learning model using the experimental method with student learning outcomes using the Direct Instruction learning model in class X SMA Negeri 1 Dampal Selatan.